Optical black holes in moving dielectrics - De Lorenci, V. A.; Klippert, R.; Obukhov, Y. N. (American Physical Soc, 2003)
We study the optical paths of the light rays propagating inside a nonlinear moving dielectric medium. For rapidly moving dielectrics we show the existence of a distinguished surface which resembles, as far as the light propagation is concerned, the event horizon of a black hole. Our analysis clarifies the physical conditions under which electromagnetic analogues of gravitational black holes can eventually be obtained in laboratory.